MEDIATION OF PROFITABILITY ON CORPORATE SOCIAL RESPONSIBILITY TO FIRM VALUE - Siti Nurul Faizah; Dharma Tintri Ediraras (JRAK, 2021)
The study aims to test and analyze the influence of CSR as measured by Economic Performance, Environmental Performance, and Social Performance on Firm Value measured using Tobin’s Q with profitability as a mediation variable. The object of this research is the information communication sector, health sector, agricultural sector, electricity sector, and real estate sector, and they were analyzed with statistical methods used is Partial Least Square (PLS). The results of this study showed that Economic Performance, Environmental Performance, and Social Performance had no effect on Return on Equity (ROE) and Tobin’s Q, while Return on Equity (ROE) had an effect on Tobin’s Q either.